The Christmas thief - Clark, Mary Higgins; Clark, Carol Higgins (New York : Simon & Schuster, 2004)
Lottery winner-turned-amateur sleuth Alvirah Meehan joins with private detective Regan Reilly to track down a ninety -foot Christmas tree, destined for display in Rockefeller Center, that vanished en route to the city.
Keywords: Reilly, Regan (Fictitious character) -- Fiction; Meehan, Alvirah (Fictitious character) -- Fiction; Christmas -- Fiction; Christmas stories; Mystery fiction